Development of E-Module (Electronic Module) Based on Ethnoscience in Natural Science Subject of Human Reproduction for Junior High Schools - Pitri, Mellia Laura; Nordin, Norazah; Langputeh, Sukree; Rakuasa, Heinrich (STKIP Pesisir Selatan, 2025)
The implementation of the 2013 curriculum was developed into a curriculum that combines various aspects, namely attitudes, knowledge, and skills. Through the 2013 curriculum, educators are required to be able to improve the quality of education so as to produce independent and creative students. Integrated science learning is presented in the context of science that includes the environment, technology, and society. Science education (science) can also be developed by relying on the uniqueness and excellence of a region, including culture and technology based on local wisdom (traditional). So that in schools there needs to be learning that contains materials based on local wisdom to prevent the loss of local wisdom from a region. This study aims to develop an e-module based on ethnoscience (local culture) for grade IX students of junior high schools/Islamic junior high schools and to determine the level of validity and practicality. The e-module developed uses the ethno-science method which consists of direct observation, explaining phenomena scientifically, and being able to draw conclusions. This research is a research and development (R&D) with the Plomp model. The validity test was conducted by 3 science lecturers from Faculty of Mathematics and Natural Sciences Universitas Negeri Padang, and the practicality test was conducted by 2 science teachers from State Junior High School 1 Painan and 3 IX.3 students, 4 IX.6 students and 20 IX.7 students at State Junior High School 1 Painan. The instruments used were validity and practicality questionnaires and data Cohen Kappa. This research produces an e-module of the human reproductive system based on ethnic with an average kappa moment of 0.90 which has a very high level of validity. The results of the teacher's practicality test and the student's practicality test obtained an average kappa moment of 0.76 and 0.81 respectively with high and very high levels of practicality.